2020
DOI: 10.1002/app.49638
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor permeability and self‐cleaning properties of solvent‐free polyurethane improved by hollow nano‐TiO2 spheres

Abstract: In the synthetic leather industry, solvent-free polyurethane film (SFPU) was poor in water vapor permeability (WVP) and washability. In this study, we introduced the hollow nano-TiO 2 spheres (HNTSs) with high photocatalytic performance and permeability performance as well as large surface area into the SFPU film to endued its superior water vapor permeability property, selfcleaning performance and water resistance. First of all, HNTSs were prepared via the controllable chemical route using HF for internal cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Recent studies showed an introduction of hollow nano-TiO 2 spheres (HNTSs) with high photocatalytic and permeability performances as well as introducing large surface area into the PU film to endue its superior water vapor permeability property, water resistance along with desirable self-cleaning performance [26].…”
Section: Super-hydrophilic (Photocatalytic) Self-cleaning Surfacesmentioning
confidence: 99%
“…Recent studies showed an introduction of hollow nano-TiO 2 spheres (HNTSs) with high photocatalytic and permeability performances as well as introducing large surface area into the PU film to endue its superior water vapor permeability property, water resistance along with desirable self-cleaning performance [26].…”
Section: Super-hydrophilic (Photocatalytic) Self-cleaning Surfacesmentioning
confidence: 99%
“…Additionally, when the adhesive force between the droplet and dust particles exceeds the adhesion between dust particles and surface. These conditions result in easy rolling of the droplet taking along the micro-sized dust particles and/or contaminants present on the surface making it a selfcleaning surface [37,38].…”
Section: Conditions For Shsmentioning
confidence: 99%
“…[25][26][27][28][29][30] The mainly is due to nanoparticles can significantly enhance the viscoelasticity and crystallization of the matrix, thereby improving the cell structure and mechanical properties of the foam. [31][32][33][34][35] Nano TiO 2 not only exhibits advantages of small particle size, large specific surface area and high surface activity, but also has strong stability, photocatalytic activity and UV shielding ability, [36][37][38] due to amphoteric oxide, a differentiated traditional nanoparticle filler generate a great expectation for foamed WPC. However, to the author's knowledge, there have been very few studies of the injection molding of WPC using nano TiO 2 particles to improve the foaming behavior and mechanical performances of PP-based WPC.…”
Section: Introductionmentioning
confidence: 99%